Prinsip Norma-norma Bertutur yang Beretiket dan Beretika dalam Alquran - Shafruddin Tajuddin (Universitas Negeri Jakarta, 2015)
In linguistic norms, the language of the Quran consists of words, sentences, and paragraphs which are full of meaning. Therefore, based on this aspect, it can be approximated as the other text that can be studied and researched through linguistic elements, as expressed in the form of linguistic structure, both textual and contextual. The language of the Quran is no longer just words, phrases, and sentences as a reading routines Muslims, but also as a sign and message and also information to communicate our Mankind that in the texts of the Quran contained linguistic discourse strands of substitutions. Therefore, this research is an ethnographic study of communication that is qualitative descriptive, and the problem is focused directly to the principles of spoken norms as the main observation variable or formal object, and can be formulated